A Homotelechelic bis‐terpyridine macroligand: One‐step synthesis and its metallo‐supramolecular self‐assembly. Issue 9 (14th February 2013) - Mansfeld, Ulrich; Winter, Andreas; Hager, Martin D.; Günther, Wolfgang; Altuntaş, Esra; Schubert, Ulrich S.
Abstract A homotelechelic macroligand bearing two 2, 2′:6′, 2″‐terpyridin‐4′‐yl units, as chain ends, is used as building block for the preparation of a linear metallo‐supramolecular chain‐extended polymer. The macroligand has been prepared by nitroxide‐mediated polymerization (NMP) of styrene using a bis‐terpyridine‐functionalized NMP initiator. The controlled character of the NMP process has been confirmed by detailed characterization of the polymer by size‐exclusion chromatography, nuclear magnetic resonance spectroscopy as well as mass spectrometry. Subsequently, the self‐assembly with FeII ions into the chain‐extended metallopolymer and the disassembly thereof, in the presence of a strong competitive ligand, has been studied by UV–vis absorption spectroscopy and diffusion‐ordered NMR spectroscopy. The reversibility of the formation of the metallo‐supramolecular material, when addressed by external stimuli, could be proven. © 2013 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2013